MANAGING RISK IN ORGANIZATION OF SPORTING EVENTS - Miodrag Koprivica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Sport Management is, without doubt, a modern, practical but at the same time scientific and theoretical trend. Starting with the definition of the word "event" as an activity that is limited in terms of time, place and a number of participants who gather together with a certain agenda in their mind, an unbreakable connection between it and sport has been made. Risks that appear in this branch of industry of sport are multiple, hardly foreseeable, and with possible long-term consequences. Precisely for that reason, it is important to provide the answers to the questions of what the crisis and crisis management in sport management are, and to establish the processes and stages of risk management